Trends in Dietary Assessment Methods among Adolescents in Indonesia: A Narrative Review - Kagami, Tazkia Putri (JURNAL KESMAS DAN GIZI (JKG), 2025)
Adolescent malnutrition remains a major public health challenge in Indonesia. Accurate dietary assessment plays a critical role in understanding adolescents’ eating patterns and their implications for nutritional status. This study aimed to identify trends in dietary assessment methods used in adolescent research in Indonesia, focusing on method variation, data collection approaches, and validation of instruments. A narrative review was conducted by screening relevant articles according to inclusion criteria, resulting in 22 eligible studies. The findings show that the most frequently used method was the Food Frequency Questionnaire (FFQ) or Semi-Quantitative FFQ (SQ-FFQ) applied in 12 studies, followed by 24-hour dietary recall, either used alone or in combination. Other methods included food records, the Dietary Quality Index for Adolescent (DQI-A), and the Dietary Diversity Score (DDS). FFQ was reported as practical and cost-effective, although most studies did not mention instrument validation. In contrast, the 24-hour dietary recall provided detailed dietary intake but required more resources and was limited by respondents’ recall ability. Combining methods, such as 24-hour recall with FFQ or food record, improved validity but increased complexity. In conclusion, dietary assessment methods in adolescent studies in Indonesia are predominantly based on FFQ and 24-hour recall, with limited evidence of validation, highlighting the need for greater methodological rigor to ensure accurate dietary assessment among adolescent.